Konsep Pendidikan Agama Islam Dalam Tinjauan Hadits: Studi Analisis tentang Hadits-hadits Pendidikan - Muhamad Basyrul Muvid (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2020)
The position of the hadith in Islamic religious education becomes the basis and foundation for the concepts, framework and design of Islamic religious education, bearing in mind that the hadith gives more concrete reasons regarding the application of various activities that must be developed in Muslim life. and living framework. The method used in this study is the study of literature, namely by collecting various references in the form of books, books, documents and articles that are assembled with the themes discussed. Results: that the concept of Islamic education in the review of educational hadiths found and analyzed included: basic education, learning obligations, educational objectives, educational institutions, learning materials (education), learning methods, educators (teachers), students (students), women's education and evaluation learning. These ten become the basic framework in building Islamic religious education in accordance with the hadith of the Prophet. So that this becomes a reference and basis in the implementation of the teaching and learning process in the world of Islamic education.Key word: Position of the Hadith, Concept of Islamic Education, Analysis of Islamic Educational Hadiths